2019
DOI: 10.22605/rrh4614
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of medical students regarding community-based teaching experiences: an observation from Bangladesh

Abstract: Introduction: Community orientation in medical education, which prepares medical students to become more effective practitioners, is now a global movement. Many medical schools around the world have adopted the concept as the main curricular framework in order to align learning programs with the needs of the community and the learner. Despite many changes over the past few decades, many improvements are still needed in medical education in Bangladesh. This study investigated medical students' perceptions of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
3
1
1
Order By: Relevance
“…This study findings were supported by the study conducted by Asaduzzaman et al revealed that majority students were satisfied to RFST activities 11 . This present study findings found to be dissimilar to the study conducted by Ahmed et al, showed that majority of the students were dissatisfied to different CMBE related activities 12 .…”
Section: Discussioncontrasting
confidence: 99%
“…This study findings were supported by the study conducted by Asaduzzaman et al revealed that majority students were satisfied to RFST activities 11 . This present study findings found to be dissimilar to the study conducted by Ahmed et al, showed that majority of the students were dissatisfied to different CMBE related activities 12 .…”
Section: Discussioncontrasting
confidence: 99%
“…Permite sentirse parte y ponerse el delantal, encontrar un rol como estudiante, involucrarse y dejar una impronta. Como los resultados publicados por Ahmed en su trabajo sobre las percepciones de los estudiantes de medicina y sus experiencias de aprendizaje basadas en la comunidad, el contacto comunitario tiene un efecto positivo en el estudiante, genera una actitud solidaria, alienta a desarrollar empatía por los sectores desatendidos de las personas en la comunidad, ayuda a aprender sobre las normas sociales, valores, creencias, los problemas, los prejuicios y la pobreza, y mejora el desarrollo de la comprensión para el cuidado de la salud 12 .…”
Section: Discussionunclassified
“…Locality: 1: Cox’s Bazar; 2: Bandarban; 3: Maulovi Bazar; 4: Manikganj; 5: Mymensingh; 6: Chittagong University Campus, Chattogram; 7: Rajshahi; 8: Jessore; 9: Narail; 10: Sylhet; 11: Chakaria Sundarban; 12: Mogra River, Netrokona; 13: Dhaka. References: A: Hasan and Rashid (2016) ; B: Rahman et al (2008) ; C: Hossain (2015) ; D: Siddiqui and Zafar (2002) ; E: Shafi and Quddus (1982) ; F: Mia et al (2016) ; G: Ahmed et al (2008) ; H: Chakraborty et al (2021) .…”
Section: Taxonomymentioning
confidence: 99%
“…More than 1,300 species of freshwater crabs have been found throughout the world ( Yeo et al 2008 ). Remarkably, only five species, namely Acanthopotamon martensi (Wood-Mason, 1875) [recorded as Potamon martensi ], Lobothelphusa woodmasoni (Rathbun, 1905) [recorded as Potamon woodmasoni ], Lamella lamellifrons (Alcock, 1909) [recorded as Paratelphusa lamellifrons ], Sartoriana spinigera (Wood-Mason, 1871) [recorded as Paratelphusa spinigera ], and Sartoriana trilobata (Alcock, 1909), have been reported from Bangladesh ( Shafi and Quddus 1982 ; Siddiqui and Zafar 2002 ; Ahmed et al 2008 ; Rahman et al 2008 ; Hossain 2015 ; Mia et al 2016 ; Hasan and Rashid 2016 ; Chakraborty et al 2021 ). There are two additional reports, i.e., Austrothelphusa transversa (von Martens, 1868) ( Ahmed et al 2008 ; Rahman et al 2008 ; Hossain 2015 ; Chakraborty et al 2021 ) and Pyxidognathus fluviatilis (Alcock, 1900) ( Ahmed et al 2008 ; Rahman et al 2008 ; Hossain 2015 ; Hasan and Rashid 2016 ; Chakraborty et al 2021 ), but the former is native to Australia and Papua New Guinea ( Esser and Cumberlidge 2008 ) and the latter species inhabits fresh, brackish, and marine waters and is not regarded as true freshwater crab ( Yeo et al 2008 ).…”
Section: Introductionmentioning
confidence: 99%